Actually existing political economies. (July 2014) - Weller, Sally; O'Neill, Phillip
In this response, we are prompted by the commentaries to discuss three issues: the need to be wary of malleability in the definitions of keywords like neoliberalism; the importance in economic geography of close study of the national scale and the relationships among state policies, economies, societies and national developmental trajectories; and the concern we have about the assumed political utility of the idea of neoliberalism now that its use is widespread. We conclude by reiterating our scepticism that all manner of changes are capable of being enrolled as aspects of 'variegated' neoliberalism. Our argument is that the important detail of political–economic change is too often overlooked as a direct consequence.